Pneumococcal Conjugate Vaccines and Otitis Media: An Appraisal of the Clinical Trials. (3rd June 2012) - Fletcher, Mark A.; Fritzell, Bernard
Abstract : Streptococcus pneumoniae is the predominant otitis media pathogen and its prevention through effective vaccination could diminish childhood illness and antibiotic use. This paper reviews 5 pneumococcal conjugate vaccine (PCV) trials that used otitis media as an endpoint: Northern California Kaiser Permanente (NCKP; vaccine, 7-valent PCV [PCV7]-CRM); Finnish Otitis Media (FinOM; vaccines, PCV7-CRM or PCV7-OMPC); Native American Trial (vaccine, PCV7-CRM); Pneumococcal Otitis Efficacy Trial (POET; vaccine, 11-valent PCV [PCV11]-PD). For the microbiological endpoint, vaccine efficacy against vaccine-serotype pneumococcal otitis media was about 60% across trials. Against the clinical endpoint of all episodes, vaccine efficacy was 7% (PCV7-CRM/NCKP), 6% (PCV7-CRM/FinOM), −1% (PCV7-OMPC/FinOM), and −0.4% (PCV7-CRM/Native American Trial); 34% against first episodes of ear, nose, and throat specialist-referral cases (PCV11-PD/POET). Both follow-up through 2 years of age, for the 5 trials, and long-term follow-up, for PCV7-CRM/NCKP and PCV7-CRM/FinOM, demonstrated greater vaccine efficacy against recurrent AOM and tympanostomy-tube placement, suggesting that vaccination against early episodes of AOM may prevent subsequent episodes of complicated otitis media. Although study designs varied by primary endpoint measured, age at follow-up, source of middle-ear fluid for culture, case ascertainment, and type of randomization, each clinical trial demonstrated vaccine efficacy against microbiological and/or clinical otitis media.